(untitled) (Fiep Bulletin - online, 2014)
Sport is an objective reality in the life of each society and represents a wide-spectral aimed movement activity of a different quality and level, for all age categories, with various connections to individual spheres of the life of society. the development of sports closely connected with the broadening of citizens’ participation in sporting activities with the aim to improve their fi tness, physical and sports performance, with health care, the infl uence on personality and effects on social relationships. to speak about sport, however, means to pay attention also to the question of education: for sport, in sport and through sport. to educate specialist and experts in the fi eld of sport is very serious work. faculty of Physical education and sports provides not only the Physical education teachers, but also highly educated experts for all fi elds of Physical education and sport. the faculty during its history prepared more than 6000 Physical education teachers, coaches and sport managers. this article provides the overview of prepared experts according to fi nished study programs. the study for this article was cross-sectional fi ve years lasting questionnaires research about students evaluating of the study at faculty of physical education and sport.